Pengembangan Video Animasi Berbasis Storytelling untuk Meningkatkan Prestasi Belajar pada Mata Pelajaran Pendidikan Pancasila - Zumrotus Sa’diyah; Nurul Mahruzah Yulia; Kuni Lu’luatun Nafisah (Pascasarjana Universitas Qomaruddin, 2024)
This study aims to describe the process and results of developing story-based animated videos for improving student learning outcomes in Pancasila Education subjects in grade IV of Madrasah Ibtidaiyah. We employed the R&D (Research and Development) method, utilizing the ADDIE model from Reiser and Mollanda. We collected data using observation instruments, interviews, questionnaires, and tests. Data analysis techniques include qualitative and quantitative analysis. The research sample involved 10 students in a small group trial and 18 students in a large group trial at MI Mansya'ul Huda. The results demonstrated a successful improvement in student learning outcomes through the development of story-based animated video media. Pre-test and post-test scores increased by 2% in the high category for the small group and 1.6% for the large group, indicating this improvement. Observations during the learning process revealed that the supporting factors for improving learning outcomes were students' concentration and focus in learning. These findings can be a reference for teachers in using interesting media and efforts to improve the learning outcomes of grade IV students of Madrasah Ibtidaiyah.